Acoustic mixing in a dome-shaped chamber-based SAW (DC-SAW) device. Issue 1 (14th November 2019) - Lim, Hyunjung; Back, Seung Min; Choi, Hyuk; Nam, Jeonghun
Abstract : A dome-shaped chamber device enables the maximizing of the effect of SAW transmitted at a Rayleigh angle. Abstract : The use of an open droplet system for surface acoustic wave (SAW)-based applications has been limited by droplet instability at high input power. This study introduces a dome-shaped chamber-based SAW (DC-SAW) device for the first time, which can be fabricated simply using a single adhesive tape and a drop of ultraviolet-curable material without soft lithography processes. The dome-shaped chamber device with a contact angle of 68° enables the maximizing of the effect of SAW transmitted at a refraction angle of roughly 22°, negating the droplet instability. The DC-SAW device was applied to acoustic mixing to estimate its capability. Acoustic mixing of two different fluids ( i.e., deionized water and fluorescent particle suspension) was demonstrated in the dome-shaped chamber device. Moreover, the effect of flow rate and applied voltage on mixing performance was estimated. With the decreasing flow rate and increasing applied voltage, mixing performance was enhanced. At an applied voltage of 20 V, mixing indices were higher than 0.9 at a total flow rate of 300 μl min −1 .